Strategy for settling claims for insurance company customers experiencing liquidity at AJB Bumiputera 1912 Medan Branch: Some notes from Islamic perspectives - Siti Saleha; Reni Ria Armayani Hasibuan; Laylan Syafina (Department of Islamic Economics, Islamic University of Indonesia, 2023)
IntroductionLiquidity is one of the problems faced by insurance companies, including AJB Bumiputera Medan Branch. This liquidity problem has an impact on many aspects of the insurance business so an appropriate strategy is needed to overcome it.ObjectivesThis research is intended to analyze the strategies used by AJB Bumiputera 1912 Medan Branch to complete claim payments to its customers. MethodThis research is field research with data collection techniques including interviews and data collection from the internet.ResultsThe step taken by AJB Bumiputera 1912 was to form a task force team for payment of delayed claims. AJB Bumiputera 1912 also implemented a benefit reduction program and a premium recovery process and sale of company assets. ImplicationsThe study highlights the importance of regulatory oversight in safeguarding policyholders rights and ensuring stability in the insurance sector.Originality/NoveltyThis research contributes to efforts to handle liquidity problems in insurance companies. Apart from that, this research also provides an Islamic perspective in handling liquidity problems in insurance companies.